Rare heterozygous GDF6 variants in patients with renal anomalies - Martens, Helge; Hennies, Imke; Getwan, Maike; Christians, Anne; Weiss, Anna-Carina; Brand, Frank; Gjerstad, Ann Christin; Christians, Arne; Gucev, Zoran; Geffers, Robert; Seeman, Tomáš; Kispert, Andreas; et al. (European journal of human genetics, 2020)
Although over 50 genes are known to cause renal malformation if mutated, the underlying genetic basis, most easily identified in syndromic cases, remains unsolved in most patients. In search of novel causative genes, whole-exome sequencing in a patient with renal, i.e., crossed fused renal ectopia, and extrarenal, i.e., skeletal, eye, and ear, malformations yielded a rare heterozygous variant in the GDF6 gene encoding growth differentiation factor 6, a member of the BMP family of ligands. Previously, GDF6 variants were reported to cause pleiotropic defects including skeletal, e.g., vertebral, carpal, tarsal fusions, and ocular, e.g., microphthalmia and coloboma, phenotypes. To assess the role of GDF6 in the pathogenesis of renal malformation, we performed targeted sequencing in 193 further patients identifying rare GDF6 variants in two cases with kidney hypodysplasia and extrarenal manifestations. During development, gdf6 was expressed in the pronephric tubule of Xenopus laevis, and Gdf6 expression was observed in the ureteric tree of the murine kidney by RNA in situ hybridization. CRISPR/Cas9-derived knockout of Gdf6 attenuated migration of murine IMCD3 cells, an effect rescued by expression of wild-type but not mutant GDF6, indicating affected variant function regarding a fundamental developmental process. Knockdown of gdf6 in Xenopus laevis resulted in impaired pronephros development. Altogether, we identified rare heterozygous GDF6 variants in 1.6% of all renal anomaly patients and 5.4% of renal anomaly patients additionally manifesting skeletal, ocular, or auricular abnormalities, adding renal hypodysplasia and fusion to the phenotype spectrum of GDF6 variant carriers and suggesting an involvement of GDF6 in nephrogenesis.
Keywords: Vesico-Ureteral Reflux; Kidney Tubules; Infant; Humans; ledvinové kanálky; kojenec; dítě; Child; Female; mutace; dospělí; Urogenital Abnormalities; lidé; Xenopus; zvířata; myši; růstový diferenciační faktor 6; Mice; buněčné linie; předškolní dítě; Adult; vezikoureterální reflux; ženské pohlaví; Cell Line; Male; Adolescent; urogenitální abnormality; Heterozygote; Animals; heterozygot; Growth Differentiation Factor 6; Mutation; mužské pohlaví; Child, Preschool; mladiství